Body size, fatness and skeletal age in female youth soccer players - Martinho, D. V.; Coelho-e-Silva, M. J.; Gonçalves Santos, J.; Oliveira, T. G.; Minderico, C. S.; Seabra, A.; Valente-dos-Santos, J.; Sherar, L. B.; Malina, R. M. (International Journal of Sports Medicine, 2023)
Growth and maturation are central concerns in the organization of training and competitions in youth sports. This study examined maturity-associated variation in body size and adiposity among adolescent girls participating in competitive age group youth soccer. The sample included 441 players 10.08-16.73 years of age. Stature and body mass were measured and body composition was predicted. The Fels method was used to estimate skeletal age. Skeletally maturity status (late, average or early maturing) was based on the difference between chronological and skeletal age for each player. Mean stature approximated the 50th percentiles of the general population in all competitive age groups, while mean weight fluctuated between 50th and 75th percentiles. Age- and maturity-specific means for estimated fat mass ranged between 18.0% and 28.2%. The number of players classified as skeletally mature increased with competitive age groups (under-13: 0%; under-15: 8%; under-17: 49%). In general, early maturing girls tended to be heavier than their age group peers and especially when compared to late maturing players.